Effect of the Building Act 2011 on compliance costs in Western Australia (Construction Economics and Building, 2014)
The Building Act 2011 commenced in Western Australia on 2 April 2012. It introduced private certification for design and construction compliance, and reduced fees and timeframes for local governments to issue permits. This research project assessed the effect of the Act on the time and cost of building approvals in WA, using an internet-based, self-completion survey to obtain feedback from people on their experience of the new building approvals process.   This research compared the cost of approval for 16 building projects under the new and old approvals processes. The research concluded that the new approvals process appears to be cost-neutral for the building industry as a whole. However, the cost of approval for the 11 building projects studied valued up to $1 million, particularly alterations to existing buildings, is an average of 4.0 times greater under the new approvals process.